Shelter seeking behaviour of dairy cattle in various types of housing systems - SHARMA, PURUSHOTIAM; SINGH, KIRAN (The Indian Journal of Animal Sciences, 2014)
The study was conducted to investigate the effect of shelter system on shelter seeking behaviour of lactating crossbred cows from March 1998 to February 1999 (summer rainy and winter seasons). Cows(30) were allotted to 3 treatment groups, randomly 10 animals in each. The treatments were loose housing (control). loose housing with central shed and closed housing. The analysis of shelter seeking behaviour revealed that unshaded manger did not discourage feeding in loose housing with central shed group in summer and rainy season i.e., 128.75 and 113.87 min, respectively, while it encouraged in winter (274.00 min). Excessive protection of closed housing resulted in considerable panting. No ranting was observed in loose housing cows. At less temperature in summer and rainy season in night, open area was more preferred by cows. In loose housing, tree-shade was the third preference. It can be concluded that cows were more comfortable in loose housing in summer and rainy season while in winter season cows were more comfortable in loose house with central shed.